A futures study on the quality of life from the point of view of Iranian youth / Sina Saeedy ... [et al.] - Saeedy, Sina; Amiri, Mojtaba; Zolfagharzadeh, Mohammad Mahdi; Eyvazi, Mohammad Rahim (Penerbit UiTM (UiTM Press), 2017)
Quality of life and satisfaction with life as tightly interconnected concepts have become of much importance in the urbanism era. No doubt, it is one of the most important goals of every human society to enhance a citizen's quality of life and to increase their satisfaction with life. However, there are many signs which demonstrate the low level of life satisfaction of Iranian citizens especially among the youth. Thus, considering the temporal concept of life satisfaction, this research aims to make a futures study in this field. Therefore, using a mixed model and employing research methods from futures studies, life satisfaction among the students of the University of Tehran were measured and their views on this subject investigated. Both quantitative and qualitative data were analysed together in order to test the hypotheses and to address the research questions on the youth discontentment with quality of life. Findings showed that the level of life satisfaction among students is relatively low and their image of the future is not positive and not optimistic. These views were elicited and discussed in the social, economic, political, environmental and technological perspectives.